Do Associations Between Perceived Environmental and Individual Characteristics and Walking Limitations Depend on Lower Extremity Performance Level?. (June 2017) - Sakari, Ritva; Rantakokko, Merja; Portegijs, Erja; Iwarsson, Susanne; Sipilä, Sarianna; Viljanen, Anne; Rantanen, Taina
Objective: The aim of this study was to analyze whether the associations between perceived environmental and individual characteristics and perceived walking limitations in older people differ between those with intact and those with poorer lower extremity performance.Method: Persons aged 75 to 90 ( N = 834) participated in interviews and performance tests in their homes. Standard questionnaires were used to obtain walking difficulties; environmental barriers to and, facilitators of, mobility; and perceived individual hindrances to outdoor mobility. Lower extremity performance was tested using Short Physical Performance Battery (SPPB).Results: Among those with poorer lower extremity performance, the likelihood for advanced walking limitations was, in particular, related to perceived poor safety in the environment, and among those with intact performance to perceived social issues, such as lack of company, as well as to long distances.Discussion: The environmental correlates of walking limitations seem to depend on the level of lower extremity performance.